KNOWLEDGE, ATTITUDE AND AWARENESS OF MEDICAL AND PARAMEDICAL STUDENTS TOWARDS COVID-19 BOOSTER VACCINATION IN A TERTIARY CARE TEACHING HOSPITAL: A SURVEY BASED CROSS-SECTIONAL STUDY. - Vedprakash Acharya; Y Roja Ramani; Pratyush Mishra; Swatantra Burman; Srikant Panigrahy (Student’s Journal of Health Research Africa, 2023)
Background: Covid-19 booster vaccination was launched in India on 15 July 2022. Medical and paramedical students play a pivotal role in motivating the general public in a given locality towards a Nation’s vaccination drive. The present study aimed to evaluate the student’s perspective towards the COVID-19 booster vaccination. Objective: To assess medical and paramedical students’ knowledge, attitude, and awareness of COVID-19 booster vaccination. Method: A cross-sectional study was carried out between 14 August 2022 to 12 September 2022 among medical and paramedical students through an online survey questionnaire. The data obtained was tabulated in Microsoft Excel. Study variables were expressed as frequencies/ percentages and graphically represented. Result: Our study revealed that MBBS (99.5%), Nursing (98.6%), and DMLT (94.8 %) students have good knowledge about the availability of booster vaccination. 97.4% of MBBS, 100% of nursing, and 90.9% of DMLT students want to motivate the general population towards immunization. At the same time 29.1% MBBS, 54.1% nursing, and 24.7% DMLT students were apprehensive about possible adverse effects of the booster vaccination. 56.7% of MBBS, 27% of nursing, and 48.1 % of DMLT students are unaware of the safety of booster doses in pregnancy and lactation. Conclusion: Awareness of booster vaccination was found to be adequate among the majority of participants. Most were confident with regard to motivating the general public towards vaccination. However, the hesitancy for the same observed towards the vulnerable population could be attributed to the paucity of information about the long-term safety, and efficacy of the booster vaccination. Recommendation: Messaging around boosters and vaccines needs to emphasize they are safe and convenient to take and that both are important.